2018
DOI: 10.1016/j.bbamcr.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Threonine 454 phosphorylation in Grainyhead-like 3 is important for its function and regulation by the p38 MAPK pathway

Abstract: The mammalian Grainyhead-like 3 (GRHL3) transcription factor is essential for epithelial development and plays a protective role against squamous cell carcinoma of the skin and of the oral cavity. A single nucleotide polymorphism (SNP) in GRHL3, rs141193530 (p.P455A), is associated with non-melanoma skin cancer in human patients. Moreover, it is known that this SNP, as well as another variant, rs41268753 (p.T454M), are associated with nonsyndromic cleft palate and that rs41268753 negatively affects GRHL3 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Our subsequent investigations have proven this hypothesis to be true. 46 TP is a characteristic motif recognized by proline-directed protein kinases. We confirmed that the T454 residue undergoes phosphorylation in human keratinocytes.…”
Section: Post-translational Modifications Of Grainyhead-like Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our subsequent investigations have proven this hypothesis to be true. 46 TP is a characteristic motif recognized by proline-directed protein kinases. We confirmed that the T454 residue undergoes phosphorylation in human keratinocytes.…”
Section: Post-translational Modifications Of Grainyhead-like Proteinsmentioning
confidence: 99%
“…Activation of p38 signaling in cells increases GRHL3 activity, and the T454 residue is important for the regulation of GRHL3 activity by the p38 MAPK pathway. 46…”
Section: Post-translational Modifications Of Grainyhead-like Proteinsmentioning
confidence: 99%
See 3 more Smart Citations